O pojęciu metody w badaniach literackich i pedagogicznych = On the Notion of Methods of Literary and Pedagogical Studies - Krauze, Urszula (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In methodical literature and in theoretical literary works written for teachers of Polish one greatly makes use of the notion of methods for indicating different ways of investigative and didactic activities without closer definition of their essence. And so arises the question, if the term "Method of analysis of a literary work" as a measure undertaken by the teacher and the pupils during literature lessons is identical with the term "Such or such teaching method"
Keywords: badania pedagogiczne; badania literackie; metoda